ADR’s Effectiveness in UAE, Is it worth it to take the Time? - Zeidan, Alaa Husni (2015)
The paper aims to discuss the most successful internationally recognized ADR's (Alternative Dispute Resolution) and the obstacles and difficulties facing the implementation the same ADR's in UAE. The paper also aims to present the relevant legal framework in the United Arab Emirates effecting the implementation of all proposed ADR's considering Cultural ,social and legal factors .Also the study will factor the existing legislation and laws along with some draft laws such as the new draft arbitration law. Finally the paper will recommend the most appropriate choice based on statistics and views gathered through a questioner addressing the subjected combined with recommendations to modify existing legislation to help improve the likelihood of a successful implementation of the selected ADR.